PENYULUHAN INDUSTRI KREATIF PADA MASYARAKAT DESA SARIWANGI AGAR TETAP PRODUKTIF DIMASA PANDEMI - Asmat Purba; Lusi Marlina; Rahmadani Hadianto; Reni Listiana (ASOSIASI IDEBAHASA KEPRI, 2022)
The Corona Virus Desease Epidemic 2019 (Covid-19) has had a significant impact on economic growth in Indonesia. On March 8, 2022, the implementation team of TEDC Polytechnic PKM activities conducted a survey on economic conditions and food prices in the Kampung Lembur Tengah RT 01/RW 05 area, Sariwangi Village, Parongpong District, West Bandung Regency. The majority of citizens who work as traders and employees of private companies have experienced the impact of declining income since the Covid-19 outbreak hit. From the results of discussions conducted with the Chairman and residents of RT 01, Sariwangi Village, it was agreed that the problems resolved in this activity were to eliminate Productive Extension during the Pandemic to Increase the Income of Residents of Central Overtime Village RT: 01 / RW: 05, Sariwangi Village, Parongpong District, West Bandung Regency. Productive activities during the pandemic took place or were carried out in people's homes on Saturday, April 16, 2022. With enthusiasm, residents follow the counseling, and it is hoped that the public will be able to create and understand the importance of creative economy counseling participants also get additional insights about making liquid soap to save expenses rather than buying liquid soap packaging directly, as well as making carrot-tofu nuggets as a cheap and healthy snack as a business idea and personal consumption.